Master Narratives of Ukrainian Political Culture - Charles McGrath (International Society of Philosophy and Cosmology, 2018)
As fighting between Russian backed rebels and government forces is taking place in eastern Ukraine, it is all the more apparent the existing political divide that exists in the country. The complex history of being subjugated by surrounding countries and major resettlements of Ukrainians is testing the country in a major way. Historically, emphasis on understanding the Soviet Union was focused on the Soviet perspective - the Soviet narratives, and most recently on reemerging Russia. As a result, little attention is placed on Ukraine's history. In order to understand the Ukrainian identity, it's necessary to know the narratives that encompass Ukraine's history. As freedom and liberty exemplifies American identity and ideology, the history of Ukraine also contains a system of stories that support Ukrainian culture. This paper, the first chapter of my dissertation, details the sources I've used to develop my methodology for understanding and analyzing narratives. As I began my research I soon realized the complexity of narratives leading me to explore the elements contained in narratives such as story, plot, character, archetypes, and the Hero's Journey or Monomyth. I will explain how I understand the meaning of narrative and master narrative, supported by relevant sources, and conclude with the methodology I will use for analysis of the master narratives that envelope the major historical events of Ukraine